Phenol-formaldehyde resols modified by boric acid - Żmihorska-Gotfryd, A. (Polimery, 2022)
Phenol-formaldehyde resol resins with improved thermal stability and flame retardancy were prepared by introducing boric acid into the matrix of PF precondensates at the condensation stage. The modified PF resols had small amounts of free monomers and high solid mass content. The thermogravimetry of cured, modified PF resols showed enhanced thermal stability in comparison with unmodified ones indicating the role of boric acid in improving thermo-oxidative resistance. Besides, the determined limited oxygen index values indicated the significantly decreased flammability of the modified resins.